Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd004014.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of pelvic organ prolapse in women

Abstract: Sacral colpopexy has superior outcomes to a variety of vaginal procedures including sacrospinous colpopexy, uterosacral colpopexy and transvaginal mesh. These benefits must be balanced against a longer operating time, longer time to return to activities of daily living, and increased cost of the abdominal approach.The use of mesh or graft inlays at the time of anterior vaginal wall repair reduces the risk of recurrent anterior wall prolapse on examination. Anterior vaginal polypropylene mesh also reduces aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
431
3
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(472 citation statements)
references
References 101 publications
21
431
3
17
Order By: Relevance
“…Sexual function of patients with dyspareunia was severely affected preoperatively. The average rate for dyspareunia reported in the literature is 12 % [31]. In our study, 15.6 % of women had dyspareunia before undergoing surgery.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Sexual function of patients with dyspareunia was severely affected preoperatively. The average rate for dyspareunia reported in the literature is 12 % [31]. In our study, 15.6 % of women had dyspareunia before undergoing surgery.…”
Section: Discussionsupporting
confidence: 46%
“…At 12 and 36 months after the procedure, the quality of life of the surveyed study participants had improved even more, and the difference to the preoperative figures remained significant. Further studies have also confirmed that mesh-based correction of pelvic organ prolapse can significantly improve patientsʼ quality of life, despite mesh-associated side-effects [26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 83%
“…Evidence supporting the value of combination surgery is still limited in these women and two reviews recognised the need for further research. 3,4 Nevertheless, many physicians combine incontinence surgery during POP repair and there are probably large regional differences in treatment. 5,6 The clinical dilemma as whether to perform combination surgery or not was the subject of two randomised trials in women with overt SUI.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used material is a surgical mesh made of polypropylene (PPL) which has long been used successfully to treat hernias. Although mesh augmented POP repair procedures have higher anatomical success rates compared to no-mesh, the functional and quality of life outcomes are not as good [6] and severe complications with life changing consequences can occur in up to 10-30% of cases [7]. Complications associated with the use of vaginal mesh are now reported widely in the media together with many litigations against physicians and manufacturers leading to the withdrawal of several mesh products from the USA market [8].…”
Section: Introductionmentioning
confidence: 99%